Impact of taxane plus bevacizumab for ovarian sex cord tumor with annular tubules. Issue 7 (6th May 2019) - Sho, Takanari; Yanazume, Shintaro; Fukuda, Mika; Togami, Shinichi; Kamio, Masaki; Kobayashi, Hiroaki
Abstract: Sex cord tumor with annular tubules (SCTAT) is rare, and 20% of SCTAT cases, excluding those associated with Peutz‐Jeghers syndrome, are clinically malignant. Limited data is available regarding the role of chemotherapy in the management of SCTAT. We encountered a 44‐year‐old woman with recurrent SCTAT complicated by peritoneal dissemination following a right adnexectomy. The surgical resection could not be performed completely due to the wide extension of the tumor. Considering the potential of becoming malignant, we chose a combination of bleomycin, etoposide and cisplatin (BEP) as postoperative chemotherapy treatment. However, the patient showed partial response following a complete BEP regimen. The patient received three courses of chemotherapy with docetaxel and carboplatin plus bevacizumab. After the combination chemotherapy, positron emission tomography‐computed tomography scan confirmed a complete response, and is currently continuing bevacizumab treatment without relapsing and having no major adverse effects from complications. This case proved the potential of a combination of taxane and bevacizumab in patients with recurrent SCTAT.